A pilot study on the proposed computer-based SDI service for SEAFDEC Aquaculture Department's scientists and researchers using MINISIS query processor - Ortega, Maribeth C.; Buenrostro, Juan Jr. C.; Sison, Josephine C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1986)
The QUERY processor of MINISIS, a relational data base management system, was used in the pilot study on computer-based SDI involving thirteen SEAFDEC researchers and scientists as users. User profiles were constructed using the ASFA (Aquatic Sciences and Fisheries Abstracts) Thesaurus and matched with as in-house data base of 5,400 records taken from the ASFA 1983 edition. Two computer runs were conducted which retrieved 373 records as hits, of which 59.5 percent were judged as relevant by the users. A high precision was therefore obtained involving about half of the profiles in the first run and subsequently the other half in the second run after profile modification.
High recall was achieved due to specificity of the profile terms and the near equivalence of the users' own terms with the terms or descriptors in the data base.
This study provided the following observations: 1) Adequate interfacing with the users proved to be a critical factor in profiling; 2) Bibliographical citations with descriptors do not provide sufficient information; inclusion of abstracts would be more effective; 3) The in-house data base contained mostly records on applied studies, with a few on basic studies. Updating this data base with records other than those found in the ASFA will provide a happy balance; 4) The fast access search capability of the QUERY processor of MINISIS, which allows easy access of the data base, makes it an applicable program for SDI.
With the results of the pilot study, a recommendation is made on implementing an SDI service in the Department using MINISIS.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: MINISIS (Information retrieval system).; Selective dissemination of information; Southeast Asian Fisheries Development Center. Aquaculture Department. Library and Documentation Service Unit